Effect of acute aerobic exercise on short-term memory, long-term memory, and working memory in medical students of a tertiary care center in India: Possible role of endocannabinoids - Madhu Chaudhary; Salman Masood; Mojahid Anwar; Shahnawaz Alam; Najmul Aqib Khan; Fareha Husain Khan; Qazi Rais Ahmad (Asian Journal of Medical Sciences, 2022)
Background: Recent studies have suggested that memory might benefit from physical exercise. Some studies also show that exercise has adverse effects on short-term memory. The number of studies on the effects of a single bout of exercise on memory is rather limited, and their results are inconsistent. In this study, we want to see the effect of a single bout of aerobic exercise on memory (short term and long term) when the learning session is before the exercise. We also want to see the effect of aerobic exercise on working memory when the learning session is after the exercise. Aims and Objectives: The aim is to find the effect of aerobic exercise on working, short-term and long-term memory. Materials and Methods: Sixty healthy medical students were divided into two groups of 30 each. Both groups were asked to listen to 20 Arabic words (proper nouns) before the experiment. Students having any knowledge of Arabic were excluded from the study. Then, one group performed high-intensity exercise on a Bicycle Ergometer for 30 min and the other group silently relaxed on a chair. The subjects were asked to repeat the words heard after 20 min of exercise and 24 h of exercise. Data were recorded manually and analyzed statistically. In another experiment, the words were listened after the exercise was over, and the subjects were asked to recall after 20 min of exercise. Unpaired t-test was applied to compare the data between the two groups, and P-value and t-value were calculated. Results: When the words were recalled 20 min after exercise, the mean number of recalled words was more in the relaxing group (RG) than in the exercise group, but the result was reverse when recall was made 24 h after the exercise, i.e., more recall by exercise group. When the learning session was after the exercise and subjects were asked to recall words 20 min after the exercise, we found more recall by RG than the exercise group. Conclusion: We conclude that aerobic exercise has an adverse effect on short-term memory and working memory but has a beneficial effect on long-term memory.